Bridging the Gap Between Data and Policies in Remote Rural Municipalities in Nepal - Walcher, Alexandra; Adhikary, Phanindra; Tamang, Urmila; Uematsu, Hiroki; Banick, Robert; Maharjan, Liza; Shrestha, Tanuja (World Bank, Washington, DC, 2021)
Nepal's transition to a federal system provides new optimism to achieve inclusive development and economic growth. However, the scarcity of locally disaggregated data and lack of capacity to use it stymie evidence-based policy decisions, especially in remote rural areas. This note summarizes our recent collaboration with International Institute for Democracy and Electoral Assistance (IDEA) to bring evidence-based policy decisions to local policy makers in remote rural municipalities in Karnali Province, western Nepal.